Dispersion relations and the spin polarizabilities of the nucleon - Drechsel, D.; Krein, G. [UNESP]; Hanstein, O. (Elsevier, 1998)
A forward dispersion calculation is implemented for the spin polarizabilities γ1, ⋯, γ4 of the proton and the neutron. These polarizabilities are related to the spin structure of the nucleon at low energies and are structure-constants of the Compton scattering amplitude at script O sign(ω3). In the absence of a direct experimental measurement of these quantities, a dispersion calculation serves the purpose of constraining the model building, and of comparing with recent calculations in heavy baryon chiral perturbation theory. © 1998 Elsevier Science B.V.
Keywords: Compton scattering; Dispersion relations; Nucleon polarizabilities; Spin content of the nucleon